Jean Baudrillard [ fatal theories - Clarke, David B. , 1964- (London ;New York : Routledge, 2009)
Jean Baudrillard was one of the most influential, radical, and visionary thinkers. Employing Baudrillard's key concepts, such as simulation, disappearance, and symbolic exchange, and deploying his
1. Introduction : the evil genius of Jean Baudrillard -- 2. The vanishing point of communication -- 3. On disappearance -- 4. Commentaries on Jean Baudrillard's "On disappearance" -- 5. Baudrillard's taste -- 6. Floral tributes, binge-drinking and the Ikea riot considered as an up-hill bicycle race -- 7. Better than butter : margarine and simulation -- 8. Baudrillard and the art conspiracy -- 9. 'Mirror, mirror' : The student of Prague in Baudrillard, Kracauer -- 10. The Gulf War revisited -- 11. Fate of the animal -- 12. Reality, now and then : Baudrillard and W-Bush's America -- 13. Baudrillard's sense of humour -- 14. The (un)sealing of the penultimate / Andrew Wernick.
Description based on print version record
Includes bibliographical references and index
Keywords: Baudrillard, Jean , -- 1929-2007; Postmodernism -- Social aspects; Sociology -- Philosophy